2020
DOI: 10.1159/000506044
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Ovarian Steroid Cell Tumor, Not Otherwise Specified, Causes Virilization in a 4-Year-Old Girl: A Case Report and Literature Review

Abstract: We report a case of a 4-year-old girl with an ovarian steroid cell tumor, not otherwise specified (SCT-NOS). She was admitted to the hospital with progressing virilization and Cushing's syndrome, which included abnormality of the perineum, hirsutism, hypertrichosis, flushing of face, hoarseness, and weight gain. Blood testing showed a significantly increased testosterone level and slightly increased cortisol level. Computed tomography scan revealed an 8.0 × 5.0 × 5.0 cm tumor of the right ovary. The patient un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Nevertheless, reported cases in children were so scarce that their typical features remained elusive. For better understanding, previously reported children cases of SCTs (n = 15) were thoroughly reviewed (Table 2) [2,[4][5][6][7][8][9][10][11][12][13][14][15]. After excluding the three cases without documented clinical manifestation and one case presenting only with mass effect, a total of 12 patients including the present case were analyzed (Table 3) [4][5][6][7][8][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, reported cases in children were so scarce that their typical features remained elusive. For better understanding, previously reported children cases of SCTs (n = 15) were thoroughly reviewed (Table 2) [2,[4][5][6][7][8][9][10][11][12][13][14][15]. After excluding the three cases without documented clinical manifestation and one case presenting only with mass effect, a total of 12 patients including the present case were analyzed (Table 3) [4][5][6][7][8][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…For better understanding, previously reported children cases of SCTs (n = 15) were thoroughly reviewed (Table 2) [2,[4][5][6][7][8][9][10][11][12][13][14][15]. After excluding the three cases without documented clinical manifestation and one case presenting only with mass effect, a total of 12 patients including the present case were analyzed (Table 3) [4][5][6][7][8][10][11][12][13][14][15]. Most of them showed heterosexual precocity (66%) with symptoms of virilization (50%), hirsutism (25%), amenorrhea (17%), hypertrichosis (17%), facial acnes (17%) and temporal balding (8%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adjuvant chemotherapy regimens currently recommended for treatment are as follows: BEP; cisplatin, doxorubicin, and cyclophosphamide; taxane and platinum; and bleomycin, vinblastine, and cisplatin. 23 27 It was reported that intraperitoneal dissemination and liver metastases were completely removed with debulking surgery, radiofrequency ablation of the liver metastasis, and adjuvant BEP (follow-up, 43 months) in a patient with a recurrent SCT-NOS occurring 5 years after the initial surgery. 28 In another study, the treatment protocol consisted of docetaxel and nedaplatin, and the patient survived for 2 years with multiple bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Yılmaz-Ağladıoğlu et al 7 reported a 13-year-old female who experienced a 6 year delay in diagnosis of SCT, NOS, by ultrasound due to presumed CAH. Yoshimatsu et al 10 documented an ovarian tumor, diagnosed as SCT, NOS, visualized on CT and MRI in a 4-year-old girl with virilization. These cases differed from ours as diagnostic imaging studies were positive.…”
Section: Discussionmentioning
confidence: 99%